The EFQM 2020 model. A theoretical and critical review - Fonseca, Luís (2021)
This research, aims to analyse the EFQM 2020 Model, supported by a literature review and content analysis, to identify its theoretical foundations and the more relevant novelties compared with the 2013 version. The EFQM 2020 Model is based on the link between an organisation’s purpose and strategy, aligned with the United Nations Sustainable Development Goals (SDGs), to simultaneously deliver performance and ensure transformation, creating enduring value for its key stakeholders and achieving remarkable results. The model adopts a strategic management lens and fits well in the Business Model description. The term excellence is no longer explicitly present, replaced by ‘outstanding’ (the best it can be). The model is less prescriptive compared to the 2013 version and comprises seven criteria grouped in three dimensions, Direction (why), Execution (how), and Results (what), supported by 23 Criterion Parts and 2 Results Criterion, plus 112 guidance points, and the RADAR assessment tool. Business Excellence Models are mainly designed with contributions from leaders and business experts. Nevertheless, on a theoretical level, several management theories support the EFQM 2020 Model. Although restricted to conceptual and theoretical analysis, this analysis can help academics and business leaders understand this novel model and support future empirical research.